2012
DOI: 10.1007/s00418-012-0954-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal chemosensation: chemosensory cells in the alimentary tract

Abstract: Sensing potentially beneficial or harmful constituents in the luminal content by specialized cells in the gastrointestinal mucosa is an essential prerequisite for governing digestive processes, initiating protective responses and regulating food intake. Until recently, it was poorly understood how the gastrointestinal tract senses and responds to nutrients and non-nutrients in the diet; however, the enormous progress in unraveling the molecular machinery underlying the responsiveness of gustatory cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 103 publications
1
52
0
Order By: Relevance
“…However, previous reports have suggested that tuft cells are often found in close proximity to neurons (14,18,39), and our collaborators have demonstrated that functional innervation regulates epithelial homeostasis and response to injury (52). Indeed, we found that DCLK1 + cells were sustained when organoids were cocultured with neurons and therefore represent, to the best of our knowledge, the first cell type that cannot be generated in organoid cultures in the absence of nonepithelial niche signals.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, previous reports have suggested that tuft cells are often found in close proximity to neurons (14,18,39), and our collaborators have demonstrated that functional innervation regulates epithelial homeostasis and response to injury (52). Indeed, we found that DCLK1 + cells were sustained when organoids were cocultured with neurons and therefore represent, to the best of our knowledge, the first cell type that cannot be generated in organoid cultures in the absence of nonepithelial niche signals.…”
Section: Discussionmentioning
confidence: 53%
“…These results suggested that nonepithelial signals might be critical for tuft cell maintenance and longevity in organoid cultures. Given that previous reports suggested an association between epithelial tuft cells and neuronal structures (14,18,39), we hypothesized that neuronal input might support tuft cell survival in colonic, intestinal, and gastric organoid cultures. To test this hypothesis, we established a coculture system of primary neurons isolated from the spinal cord (40) To test whether functional innervation was associated with tuft cell survival in vivo, we examined paired biopsies from intestinal transplant patients (n = 2) and found that while the transplanted graft (which was extrinsically denervated) lacked DCLK1 + cells, the endogenous intestine (which was normally innervated) had a normal complement of DCLK1 + cells (Supplemental Figure .…”
Section: Dclk1 + Cells In In Vitromentioning
confidence: 99%
“…These receptors are also expressed in gastrointestinal tract [3,4], where they play important roles in nutrient assimilation and endocrine responses [5,6]. Recently, several studies focused on the connection between the activation of gut-expressed taste receptor and the hormonal secretion [7,8]. Glucagon-like peptide-1 (GLP-1), an incretin hormone which augments the release of insulin, is secreted in a taste receptor-dependent manner by enteroendocrine L cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…and inhibits the release of the feeding-stimulatory gut hormone ghrelin (3,19). Consequently, deletion of gut fatty acid sensors would be expected to reduce the satiating response to fat, and this has been documented in CD36 KO mice (27,28).…”
mentioning
confidence: 95%